2017
DOI: 10.32413/pjph.v7i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practices Regarding Vitamin D Among Students of Saidu Medical College, Swat

Abstract: Background: Vitamin D is also known as the “Vitamin of Sun”. More than one billion people are suffering from Vitamin D deficiency globally; it is an epidemic and a very serious global public health problem. In South Asia, Vitamin D deficiency is quite prevalent. Many recent studies have shown that vitamin D helps in preventing cancer, cardiovascular diseases and diabetes.Objectives: To assess the knowledge, attitude, dietary and sunshine practices regarding Vitamin D among students of Saidu Medical College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…In the current study, most of the participants had excellent knowledge about vitamin D (95.10%). The results are consistent with other study results 17,18 . In those studies the enrolled samples were medical students, this could explain their good level of knowledge about vitamin D 17,18 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, most of the participants had excellent knowledge about vitamin D (95.10%). The results are consistent with other study results 17,18 . In those studies the enrolled samples were medical students, this could explain their good level of knowledge about vitamin D 17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…The majority of the students were aware of the fact that sunlight is one of the main sources of vitamin D (97.9%). These findings are comparable with other studies 14,18 . Despite the awareness of the study participants about the role of sunlight in endogenous vitamin D synthesis, only 10.5% of the participants reported outdoor activities in their daily life.…”
Section: Discussionsupporting
confidence: 93%
“…Of the 575 respondents, 64.8% knew about vitamin D and its role in health; 57.4% correctly identified the sun as a source of vitamin D, 55.1% knew its effects on health and 5.8% knew about food sources of vitamin D; nevertheless, their specific knowledge of dietary food sources was poor. A lack of consistency was observed between attitude towards sunlight exposure and knowledge of vitamin D. Haq et al (2017), in their study among medical college students in Swat, Pakistan, found that student's knowledge about vitamin D was good but their attitude towards sun exposure and dietary practices did not correspond to their knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…The study showed that health care workers working in Addis Ababa and rural highland areas in Ethiopia has a better practice of adult vitamin D service compared with those living in rural lowland areas which could be related to the physicians misunderstanding that people living in arid lowland areas have a better access to sunlight exposure though studies in the middle East indicated the opposite (12,34).…”
Section: Discussionmentioning
confidence: 96%